2010
DOI: 10.1111/j.1740-0929.2010.00750.x
|View full text |Cite
|
Sign up to set email alerts
|

Effects of starch and protein sources on starch disappearance in the gastrointestinal tract of Hanwoo (Korean native) steers

Abstract: Hanwoo (Korean native) steers (274.8 +/- 4.6 kg) with ruminal and duodenal cannulae were used in a 4 x 4 Latin square design experiment to examine the effects of dietary treatments on starch disappearance in the gastrointestinal tract. Dietary treatments consisted of concentrate that were based on ground corn with soybean meal (C-SBM), ground corn with corn gluten meal (C-CGM), ground barley with soybean meal (B-SBM) and ground barley with corn gluten meal (B-CGM). Although the intakes of starch and protein fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
7
1
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(12 citation statements)
references
References 31 publications
3
7
1
1
Order By: Relevance
“…In agreement with our data, Khorasani et al (1994Khorasani et al ( , 2001 and Kim et al (2010) reported no differences in ruminal pH and total VFA concentrations between corn and barley but McCarthy et al (1989), Taniguchi et al (1991) and Khorasani et al (2001) reported greater total VFA concentrations in barley-based diets and it is due to the greater rate of degradation of nonstructural carbohydrates of barley than of corn. Molar proportions of individual VFA were not affected by the treatments, except for valerate, in the present experiment.…”
Section: Resultssupporting
confidence: 81%
See 4 more Smart Citations
“…In agreement with our data, Khorasani et al (1994Khorasani et al ( , 2001 and Kim et al (2010) reported no differences in ruminal pH and total VFA concentrations between corn and barley but McCarthy et al (1989), Taniguchi et al (1991) and Khorasani et al (2001) reported greater total VFA concentrations in barley-based diets and it is due to the greater rate of degradation of nonstructural carbohydrates of barley than of corn. Molar proportions of individual VFA were not affected by the treatments, except for valerate, in the present experiment.…”
Section: Resultssupporting
confidence: 81%
“…Molar proportion of valerate was significantly greater (p<0.05) from 4 h to 6 h for the barley-based diets than for corn-based diets in the present experiment, in agreement with Overton et al (1995). Comparing with the previous experiment (Kim et al, 2010), there was a difference in concentrate DM intake (1.7 vs. 1.2% of BW). This contributed to the differences in total VFA (128 vs. 100 mM) between experiments.…”
Section: Resultssupporting
confidence: 80%
See 3 more Smart Citations